Glucagon-like peptide (GLP)-1 regulation of lipid and lipoprotein metabolism - Hoffman Simon; Adeli Khosrow (Medical Review, 2024)
Metabolic health is highly dependent on intestinal and hepatic handling of dietary and endogenous lipids and lipoproteins. Disorders of lipid and lipoprotein metabolism are commonly observed in patients with insulin resistant states such as obesity, metabolic syndrome, and type 2 diabetes. Evidence from both animal models and human studies indicates that a major underlying factor in metabolic or diabetic dyslipidemia is the overproduction of hepatic and intestinal apolipoprotein (apo)B-containing lipoprotein particles. These particles are catabolized down into highly proatherogenic remnants, which can be taken up into the arterial intima and promote plaque development. Several gut-derived peptides have been identified as key regulators of energy metabolism; one such peptide is the incretin hormone glucagon-like peptide (GLP)-1. Our laboratory has previously demonstrated that GLP-1 can signal both centrally and peripherally to reduce postprandial and fasting lipoprotein secretion. Moreover, we have demonstrated that GLP-1 receptor (GLP-1R) agonists can ameliorate diet-induced dyslipidemia. Recently, we published evidence for a novel vagal neuroendocrine signalling pathway by which native GLP-1 may exert its anti-lipemic effects. Furthermore, we demonstrated a novel role for other gut-derived peptides in regulating intestinal lipoprotein production. Overall, ample evidence supports a key role for GLP-1R on the portal vein afferent neurons and nodose ganglion in modulating intestinal fat absorption and lipoprotein production and identifies other gut-derived peptides as novel regulators of postprandial lipemia. Insights from these data may support identification of potential drug targets and the development of new therapeutics targeting treatment of diabetic dyslipidemia.